A simple reversed phase high-performance liquid chromatography (HPLC) method for determination of in situ gelling curcumin-loaded liquid crystals in in vitro performance tests - Fonseca-Santos, Bruno [UNESP]; Gremião, Maria Palmira Daflon [UNESP]; Chorilli, Marlus [UNESP] (Scientific Scholar, 2017)
A simple, rapid, and sensitive analytical procedure has been developed and validated for the in vitro measurement of curcumin in samples from mucosae retention studies. Curcumin was analyzed by HPLC using a C18 column with UV detection at 425 nm. The mobile phase was acetonitrile and water (50:50 v/v) acidified with 2% acetic acid at a flow rate of 1.2 mL min−1. The curve range was linear for the receptor solution concentration range 0.5–75 μg mL−1. The specificity showed no interference with the biological matrix and excipients of the acceptor media. Intra and inter-day accuracy, and precision values were lower than 5% and were not statically different (P < 0.05). Recoveries ranged from 99.7% to 108%. The limits of detection and quantitation were 11.61 and 500 ng mL−1, respectively. The method is adequate to assay curcumin from esophageal porcine samples, enabling the determination of penetration profiles for in situ gelling curcumin-loaded liquid crystals by in vitro studies, and fulfilled the requirements for reliability and feasibility for application to the quantitative analysis of curcumin in porcine esophageal mucosae.
Keywords: Curcumin; High-performance liquid chromatography; Liquid crystals; Performance tests; Validation